Once a spy eaudiobook Rogues redeemed series, book 4. - Putney, Mary Jo (Rogues Redeemed, 2019)
Love and survival in the shadow of Waterloo . . . Wearied by his years as a British intelligence officer, Simon Duval resigns his commission after Napoleon's abdication. Hoping to find new meaning in his life, he returns to England, where he discovers his cousin's widow, Suzanne Duval, the Comtesse de Chambron. Working as a seamstress, living in reduced circumstances, Suzanne has had a life as complicated as Simon's. While both believe they are beyond love, their sympathetic bond leads him to propose a marriage of companionship, and Suzanne accepts. She didn't want or expect a true marriage, but as Suzanne joins Simon in a search for his long missing foster brother, warmth and caring begin to heal both their scars-and a powerful passion sparks between them. Then news from France threatens to disrupt their happiness. Napoleon has escaped from Elba and Wellington personally asks Simon to help prevent another devastating war. Only this time, Simon does not go into danger alone. He and Suzanne will face deadly peril together, and pray that love will carry them through . . .